Generalized Form of Difference Sequence Space of Fuzzy Real Numbers Defined by Orlicz Function - Paudel, Gyan Prasad; Sahani, Suresh Kumar; Pahari, Narayan Prasad (Nepal Journal of Mathematical Sciences, 2022)
See Full Text.